2016
DOI: 10.1007/s00198-016-3494-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and clinical performance of kyphoplasty and SpineJack® procedures in the treatment of osteoporotic vertebral compression fractures: a pilot, monocentric, investigator-initiated study

Abstract: This pilot study showed that both techniques were safe and efficient for the osteoporotic VCF treatment. Radiological results indicate that the SpineJack® procedure has a higher potential for vertebral body height restoration and maintenance over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 22 publications
4
57
1
Order By: Relevance
“…However, in both studies, loss of correction was observed with the SpineJack® in the follow‐up period, but was still significantly superior to the baseline value. Interestingly, no correction was achieved with BK in the study by Noriega et al In our study, a significant correction was achieved postoperatively with the SpineJack®, but the KA correction was lost and not significantly different from the baseline at the end of follow‐up.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…However, in both studies, loss of correction was observed with the SpineJack® in the follow‐up period, but was still significantly superior to the baseline value. Interestingly, no correction was achieved with BK in the study by Noriega et al In our study, a significant correction was achieved postoperatively with the SpineJack®, but the KA correction was lost and not significantly different from the baseline at the end of follow‐up.…”
Section: Discussioncontrasting
confidence: 53%
“…Thereafter, the expanded implant is contained in injected cement, which stabilizes the fracture and maintains the vertebral body reduction. Since the introduction of the SpineJack®, a few clinical studies have reported superior results for the SpineJack® with regard to the restoration of VBH and correction of KA when compared with vertebroplasty and BK . However, in both studies, loss of correction was observed with the SpineJack® in the follow‐up period, but was still significantly superior to the baseline value.…”
Section: Discussionmentioning
confidence: 94%
“…After the reduction, PMMA is injected into the vertebral body. The use of two devices symmetrically positioned inside the vertebral body allows a homogeneous spreading of the PMMA (18,19). The expansion of the device causes a preferential direction of the flow of the PMMA thus reducing the risk of leakage.…”
Section: Discussionmentioning
confidence: 99%
“…When injected, the inter-digitation of the PMMA produces a large contact area below the midline; this is essential in order to confer stability to the vertebral body. The device has a "self-locking security system" that allows to significantly reduce the risk of vertebral endplate breakage (6,19). In case of corpectomy and expandable titanium cage implant, the procedure-related complication rate is potentially higher: this approach in fact may involve severe intraoperative bleeding and long surgical times, leading to increased postoperative pain, convalescence, and risk of complications (20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous percutaneous techniques have then been developed to improve reduction of fractures, mainly by using intravertebral devices such as balloon kyphoplasty (BKP) [13] and more recently the SpineJack® (Vexim) [14]. The effectiveness of the Spinejack® being already established in acute OVCFs [15,16], the purpose of this study was to evaluate the feasability of vertebral augmentation with the SpineJack® in chronic OVCFs (i.e. : > 6 weeks) with important kyphosis.…”
Section: Introductionmentioning
confidence: 99%